A Literature Review on Capital Structure, Ownership Structure, and Firm Performance - EL FARISSI , Inass; AYACHE , Basma; AMCHAAROU , Houda (Revue Internationale des Sciences de Gestion, 2026)
This paper presents a systematic review on the interactions between capital structure, ownership structure, and firm performance, with the aim of identifying key research trends and highlighting gaps in the literature. Drawing on theoretical and empirical contributions published in journals in finance, economics, management, and governance, our study analyzes the mechanisms through which financing choices and ownership structure influence firm performance. The article reveals the existence of heterogeneous empirical results regarding the impact of financial leverage on performance and underscores the growing importance of governance mechanisms, particularly ownership structure, in explaining these divergences. This review contributes to the literature by providing a synthesis of existing research, identifying the main factors explaining the diversity of empirical results, and suggesting several avenues for future research on the interactions between governance, financing, and performance.